Pengaruh Brand Image, Kualitas Pelayanan, Variasi Menu Dan Store Atmosphere, Terhadap Keputusan Pembelian Di Cafe Ungu Dengan Harga Sebagai Variabel Moderasi - M. Agriawan Satria Utama; Miftahuddin, Muchammad Agung; Santoso, Suryo Budi; Fakhruddin, Iwan (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the influence of brand image, service quality, menu variety, store atmosphere, and price on consumer purchase decisions at Café Ungu Amikom Purwokerto, with price as a moderating variable. The study was motivated by increasing competition in the café industry, requiring managers to understand factors shaping overall customer experience. Data were collected through questionnaires using purposive sampling, involving 360 respondents. Multiple regression analysis was conducted using SmartPLS 4. The results indicate that brand image, service quality, menu variety, store atmosphere, and price positively influence purchase decisions. However, price does not positively moderate these relationships.